2021
DOI: 10.1109/access.2021.3092407
|View full text |Cite
|
Sign up to set email alerts
|

Assistive Technology for Elderly Care: An Overview

Abstract: Global demographic changes have resulted in a growing technological demand to meet the arisen social needs. In particular, the increasingly ageing population requires assistive technologies to stay at home for longer independently while receiving continuous healthcare. In this sense, a wide academic and industrial research is taking place, introducing these technologies in hospitals and rehabilitation centres. This paper aims at providing an overview of research projects for elderly care and assistance, focusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…(1) In terms of identifying whole process elderly health information modules, through in-depth interviews with medical and nursing staff common diseases such as cardiovascular, cerebrovascular and respiratory diseases, and combined with the results of literature research, five elderly health information modules were finally identified. (2) In the identification of elderly medical health information chain, the information was mainly obtained through the interviews with the staff of the data management sections and the retrieval of public information of the hospitals mentioned above, and thus the current situation, obstacles, breakthroughs and expected goals were found. (3) As for the identification of the elderly care information chain, the information was obtained through the interviews with the staff of the data management departments and the retrieval of public information of the elderly care institutions mentioned above, after analyzing the relevant information, the current situation, difficulties, breakthroughs and expected goals of elderly care information chain construction were found.…”
Section: Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…(1) In terms of identifying whole process elderly health information modules, through in-depth interviews with medical and nursing staff common diseases such as cardiovascular, cerebrovascular and respiratory diseases, and combined with the results of literature research, five elderly health information modules were finally identified. (2) In the identification of elderly medical health information chain, the information was mainly obtained through the interviews with the staff of the data management sections and the retrieval of public information of the hospitals mentioned above, and thus the current situation, obstacles, breakthroughs and expected goals were found. (3) As for the identification of the elderly care information chain, the information was obtained through the interviews with the staff of the data management departments and the retrieval of public information of the elderly care institutions mentioned above, after analyzing the relevant information, the current situation, difficulties, breakthroughs and expected goals of elderly care information chain construction were found.…”
Section: Materials and Methodsmentioning
confidence: 99%
“…to live in elderly care institutions (2). However, with the limited resources available from the government, society, and families, securing the quality of life for the elderly is in conflict with the rapid increase in the number of elderly people.…”
mentioning
confidence: 99%
“…The study by Ester et al ( 60 ) discusses assistive technology used by older adults such as robot assistants and physical and cognitive rehabilitation for older adults. Physical rehabilitation, speech therapy, social assistants, healthcare companion robots, and many similar such assistive technologies have been discussed by the authors.…”
Section: Application Fields Of Assistive Technologymentioning
confidence: 99%
“…New trends emerged in the elderly care services research make it necessary to review the literature, to visualize research hotspots, and to identify future directions. However, current researches focus on a particular pension services such as one specific pension model [9], assistive technologies supporting elderly services [10], and pension services in a certain country [11]. There is lack a comprehensive and just literature review that can display the evolution of research hotspots and reveal research frontier in extant reviews.…”
Section: Introductionmentioning
confidence: 99%